2017
DOI: 10.1111/1751-7915.13035
|View full text |Cite
|
Sign up to set email alerts
|

Detection of novel syntrophic acetate‐oxidizing bacteria from biogas processes by continuous acetate enrichment approaches

Abstract: SummaryTo enrich syntrophic acetate‐oxidizing bacteria (SAOB), duplicate chemostats were inoculated with sludge from syntrophic acetate oxidation (SAO)‐dominated systems and continuously supplied with acetate (0.4 or 7.5 g l−1) at high‐ammonia levels. The chemostats were operated under mesophilic (37°C) or thermophilic (52°C) temperature for about six hydraulic retention times (HRT 28 days) and were sampled over time. Irrespective of temperature, a methane content of 64–69% and effluent acetate level of 0.4–1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 64 publications
2
32
0
Order By: Relevance
“…The FTHFS gene was amplified with previously developed primers ( 21 ), with some modifications ( 54 ). For the restriction reactions, the amplified FTHFS gene fragment of ∼635 bp was purified using the E-Gel Safe Imager system and E-Gel SizeSelect 2% agarose gels (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…The FTHFS gene was amplified with previously developed primers ( 21 ), with some modifications ( 54 ). For the restriction reactions, the amplified FTHFS gene fragment of ∼635 bp was purified using the E-Gel Safe Imager system and E-Gel SizeSelect 2% agarose gels (Invitrogen).…”
Section: Methodsmentioning
confidence: 99%
“…The known SAOB that could be detected were Syntrophaceticus and Tepidanerobacter, both indicators for the pH 7.0-8.5 cluster and members of the order Thermoanaerobacterales [93,106]. Although the only cultivated member of the genus Syntrophaceticus (S. schinkii) is mesophilic, 16S rRNA genes of related species have been detected in various thermophilic sludge communities [93,107]. The thermotolerant species Tepidanerobacter acetatoxidans was isolated from a mesophilic methanogenic system and is able to perform both acidogenesis and SAO [106].…”
Section: Effect Of Ph On Physiochemical and Microbiological Aspects Omentioning
confidence: 99%
“…Hence, it is suggested that no H 2 limitation was prevalent within the analyzed thermophilic biogas fermenter and/or M. wolfeii is syntrophically connected with H 2 supplying bacteria. Syntrophic interactions and especially the syntrophic hydrogen transfer between Bacteria and hydrogenotrophic Archaea are often described in the context of the biogas process [74][75][76]. Syntrophic growth of M. thermautotrophicus with Syntrophothermus lipocaldicus revealed, that the methyl-coenzyme M reductase I (Mcr) was preferred instead of methyl-coenzyme M reductase II (Mrt), in contrast to expression of both enzymes in pure culture of M. thermautotrophicus [77].…”
Section: Reconstruction and Transcriptional Activity Of The Hydrogenomentioning
confidence: 99%